2012
DOI: 10.1073/pnas.1203118109
|View full text |Cite
|
Sign up to set email alerts
|

Remote control of DNA-acting enzymes by varying the Brownian dynamics of a distant DNA end

Abstract: Enzyme rates are usually considered to be dependent on local properties of the molecules involved in reactions. However, for large molecules, distant constraints might affect reaction rates by affecting dynamics leading to transition states. In single-molecule experiments we have found that enzymes that relax DNA torsional stress display rates that depend strongly on how the distant ends of the molecule are constrained; experiments with different-sized particles tethered to the end of 10-kb DNAs reveal enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…The comparisons of the rates of recombinase association with target sites and of synapse formation made here among λ Int, Cre and Flp are valid, as they were obtained by using similar TPM analyses. However, these rates could be influenced by the force exerted on the DNA by the tethered particle whose motions are tracked (36,53). The association constants for the non-productive complexes and the pre-synaptic state estimated for Flp are within a factor of two of the corresponding values for Cre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparisons of the rates of recombinase association with target sites and of synapse formation made here among λ Int, Cre and Flp are valid, as they were obtained by using similar TPM analyses. However, these rates could be influenced by the force exerted on the DNA by the tethered particle whose motions are tracked (36,53). The association constants for the non-productive complexes and the pre-synaptic state estimated for Flp are within a factor of two of the corresponding values for Cre.…”
Section: Discussionmentioning
confidence: 99%
“…Under the conditions used in the topological studies, the life-time of the Flp(Y343F) established synapse may be sufficiently long relative to the rate of topo I or ligase action. Alternatively, during the TPM assays, the force exerted on the DNA by the movement of the attached polystyrene bead may destabilize the synapse in the absence of strand cleavage (36,53). …”
Section: Discussionmentioning
confidence: 99%
“…Previous single-molecule experiments provided an incisive tool for elucidating variation in emissive spectra (8) and for switching between states with different emissive spectra (9) and lifetimes (10). These experiments, however, relied on immobilization by attachment chemistry or nonspecific surface association that may alter protein structure significantly or introduce an artificial near-environment (11)(12)(13), producing greater heterogeneity in fluorescence intensities and lifetimes. Indeed, modeling of these two sets of previous room temperature experiments yielded conflicting results, which the authors suggest may arise from differing immobilization schemes (14).…”
mentioning
confidence: 99%
“…Experiments have shown that the activity of topoisomerase IB, an enzyme which relaxes DNA supercoils, is sensitive to the viscous drag at the end of a microns-long DNA molecule [38]. We thus predict that the activity of enzymes modulating DNA twist will also sensitively depend on boundary conditions.…”
Section: Resultsmentioning
confidence: 99%